Hydrogeochemical characteristics of shallow groundwater and salinization evaluation in the coastal aquifers of Cangzhou, China - Li, Hui; Liu, Yang; Wang, Chaoyue; Yu, Kaining; Zhou, Yahong; Fu, Xiaogang; Bai, Xiaoli; Li, Xin (Frontiers in Marine Science, 2024)
To investigate the hydrogeochemical characteristics of shallow groundwater and evaluate groundwater salinization state in Cangzhou, China, two sampling campaigns have been conducted. In summer, 33 groundwater samples, 3 seawater samples and 5 river water samples were collected. In winter, 22 groundwater samples were collected. The hydrochemical type was determined by the Piper diagram. Evolution mechanisms of groundwater were analyzed by the Gibbs diagram. The trend of de-salinization or salinization of groundwater was determined by the hydrochemical facies evolution diagram. The groundwater salinization grade was evaluated by both the seawater intrusion groundwater quality index (GQISWI) and the attribute recognition model based on entropy weight (ARMEW). The Piper diagram shows that Na+ is the dominant cation and Cl- is the dominant anion in shallow groundwater, and the groundwater in this area is mainly of Cl-Na type followed by Cl-Ca·Mg type. The evaporation-crystallization process has significant influence on the evolution of saline groundwater. In summer, most brackish groundwater exhibit compositions of the freshening stage with direct cation exchange, and most saline groundwater is mainly at the seawater intrusion stage with reverse cation exchange. In winter, compared to the summer season, more groundwater samples in the middle of study area exhibit intrusion trend, and without obvious Na-HCO3 facies. In summer, values of GQISWI range from 20.47 to 75.38 with an average of 59.31. The GQISWI gradually increases from east to west, denoting the degree of groundwater salinization is alleviated from coast to inland. In winter, values of GQISWI range from 54.47 to 79.09 with an average of 66.00, slightly higher than that in summer. The proportion of no salinization (Grade I), minor salinization (Grade II) and serious salinization (Grade III) of groundwater samples in Cangzhou identified by ARMEW is 3.0%, 21.2% and 75.8% in summer, respectively. In winter, the proportion is 9.1% for Grade II and 90.9% for Grade III. The GQISWI index shows the largest area of Grade II, and ARMEW presents the largest area of Grade III in both seasons. Compared with GQISWI index, ARMEW model gives more conservative evaluation results of groundwater salinization. The results provide useful information on the groundwater salinization status for the local area, and help for the management of groundwater resources in Cangzhou.